Covalent Organic Frameworks for the Capture, Fixation, or Reduction of CO2 - Ozdemir, John; Mosleh, Imann; Abolhassani, Mojtaba; Greenlee, Lauren F.; Beitle, Robert R.; Beyzavi, M. Hassan (Frontiers in Energy Research, 2019)
Covalent organic frameworks (COFs) are porous crystalline organic polymers which have been the subject of immense research interest in the past 10 years. COF materials are synthesized by the covalent linkage of organic molecules bonded in a repeating fashion to form a porous crystal that is ideal for gas adsorption and storage. Chemists have strategically designed COFs for the purpose of heterogeneous catalysis of gaseous reactants. Presented in this critical review are efforts toward developing COFs for the sequestration of CO2 from the atmosphere. Researchers have determined the CO2 adsorption capabilities of several COFs is competitive with the highest surface area materials. Engineering the pore environment of COFs with chemical moieties that interact with CO2 have increased the CO2 adsorption performance. The installation of CO2 binding moieties in the COF has made possible the selective adsorption of CO2 over other gases such as N2. The high degree of control of internal pore composition in COFs is coupled with high CO2 adsorption to develop heterogeneous catalysts for the conversion of CO2 to value added products. Two notable examples of this catalysis are the fixation of CO2 to epoxides for the synthesis of cyclic carbonates and the reduction of CO2 to CO. Recent examples of COFs for the capture of CO2 will be discussed followed by COF catalysts which use CO2 as a feedstock for the production of value-added products.